Expression of VEGF-A And COX-2 mRNA in non-steroidal anti-inflammatory drugs treated rat primary colonic fibroblast - Andrew Limavanady; Jonathan J; Gloria Evita Thalia; Rasya Mayora; Ade Saputri; Rahmi Ayu Wijayaningsih; Eko Purnomo; Fara Silvia Yuliani; Woro Rukmi Pratiwi; Dwi Aris Agung Nugrahaningsih (Indonesian Journal of Pharmacology and Therapy, 2020)
Non-steroidal anti-inflammatory drugs (NSAIDs) is often used to shorten recovery time after surgery, including after colon anastomosis surgery. Studies showed that NSAIDs might involve in the development of colon anastomotic leakage. However, the effect of NSAIDs in colon anastomosis leakage is still a subject of controversy. Studies indicated that selectivity of COX-2 might have a role in the deleterious effect of NSAIDs in colon anastomosis. Disruption of VEGF-A by NSAIDs also suspected to be the culprit in the development of anastomosis leakage during NSAIDs treatment. This study aimed to investigate the NSAIDs effect toward VEGF-A and COX-2 mRNA in rat primary colonic fibroblast. The in vitro study was conducted using fibroblast isolated from rat colon. The isolated fibroblast was divided into 4 groups of treatment i.e.controlgroup, acetaminophen group, metamizole group, and ketorolacgroup. After 48 h of treatment, the cell was harvested and the RNA was isolated. The expression of VEGF-A and COX-2 mRNA was conducted using semi-quantitative PCR(sq-PCR). Both VEGF-A and COX-2 were not expressed in untreated rat colon fibroblast. However, VEGF-A mRNA washighly expressed in the ketorolacgroup. Interestingly, COX-2 mRNA couldbe seen in the ketorolac and metamizole groups but not in the acetaminophen group. The COX-2 mRNA expression wasthe highest in ketorolac treated rat colon fibroblast. It can be concluded that the effect of various kinds of NSAIDs towards VEGF-A and COX-2 mRNA expression of colon fibroblasts is different. This condition is duetotheir different inhibitory selectivity towards COX-1 and COX2.